A device for stereotaxic viral delivery into the brains of neonatal mice - Pedro R Olivetti; Clay O Lacefield; Christoph Kellendonk (BioTechniques)
The increasing interest in manipulating neural circuits in developing brains has created a demand for reliable and accurate methods for delivering viruses to newborn mice. Here we describe a novel 3D-printed mouse neonatal stereotaxic adaptor for intracerebral viral injection that provides enhanced precision and reliability. Using this device, we injected A2a-Cre mice with a Cre-dependent hM4D-mCherry viral construct at postnatal day 1 (P1) and demonstrated selective expression in the striatal indirect pathway neurons on days P7, P11 and P25. Similarly, dopaminergic midbrain neurons were selectively targeted with a Cre-dependent green fluorescent protein virus in Dat-IRES-Cre neonates and expression examined at P25. Our open-source neonatal stereotaxic mouse adaptor facilitates neonatal neuronal targeting, which should improve the ability to label and modify neural circuits in developing mouse brains.